2011
DOI: 10.1111/j.1365-2141.2011.08883.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide copy number analysis of paediatric Burkitt lymphoma using formalin‐fixed tissues reveals a subset with gain of chromosome 13q and corresponding miRNA over expression

Abstract: SUMMARY The majority of paediatric Burkitt lymphoma (pBL) patients that relapse will die of disease, but markers for this high-risk subset are unknown. MYC translocations characterize pBL, but additional genetic changes may relate to prognosis and serve as potential biomarkers. We utilized a molecular inversion probe single nucleotide polymorphism assay to perform high resolution, genome-wide copy number analysis on archival formalin-fixed, paraffin-embedded pBL and germline tissues. We identified copy number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 32 publications
7
48
0
Order By: Relevance
“…15,16 MCL1 is located on 1q21.2, a genomic region amplified in approximately 25% of pBL cases. 17 Amplification of MCL1 has been described in a BL subline 18 but has not been reported in primary BL samples. MCL1 overexpression may be clinically relevant because it has been linked to chemotherapy resistance, 18,19 and several inhibitors that may target MCL1 are in clinical development (supplemental Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…15,16 MCL1 is located on 1q21.2, a genomic region amplified in approximately 25% of pBL cases. 17 Amplification of MCL1 has been described in a BL subline 18 but has not been reported in primary BL samples. MCL1 overexpression may be clinically relevant because it has been linked to chemotherapy resistance, 18,19 and several inhibitors that may target MCL1 are in clinical development (supplemental Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Aberrant CGH profiles were detected in 17/26 cases (65%) of classic BL in one study (Salaverria et al, 2008) while another CGH study found copy number alterations in 7/13 patient samples (Toujani et al, 2009). A high-resolution SNP analysis of 39 frozen BL samples found a total of 308 gains and 220 losses (Scholtysik et al, 2010), and high resolution gene copy number analysis of formalin-fixed, paraffin-embedded paediatric BL samples identified 32 gains and 30 copy number losses with at least one gain or loss in 64% of samples (Schiffman et al, 2011). Similar to the conventional cytogenetic findings described earlier, changes on chromosome 1q, 13q, and 17p were commonly identified.…”
Section: Array Cgh and Snp Arraysmentioning
confidence: 98%
“…4, 12 We also reviewed our published SNP array data on 27 Burkitt Lymphoma (BL) samples. 13 In addition, kappa-expressing B-cells, lambda-expressing B-cells and control monocytes were separated from the whole blood of 10 healthy volunteers. DNA was isolated from the 25 Utah B-ALL samples, 11 B-ALL cell lines, 5 TARGET B-ALL samples and the healthy volunteers (RecoverAll Total Nucleic Acid Isolation Kit, Ambion, Austin, TX, USA; see Supplementary Information).…”
mentioning
confidence: 99%